NMR chemical shielding and spin-spin coupling constants of liquid NHȝ: a systematic investigation using the sequential QM/MM method - Gester, Rodrigo M. (2009)
The NMR spin coupling parameters, ¹J(N,H) and ²J(H,H), and the chemical shielding, σ(15N), of liquid ammonia are studied from a combined and sequential QM/MM methodology. Monte Carlo simulations are performed to generate statistically uncorrelated configurations that are submitted to density functional theory calculations. Two different Lennard−Jones potentials are used in the liquid simulations. Electronic polarization is included in these two potentials via an iterative procedure with and without geometry relaxation, and the influence on the calculated properties are analyzed. B3LYP/aug-cc-pVTZ-J calculations were used to compute the ¹J(N,H) constants in the interval of −67.8 to −63.9 Hz, depending on the theoretical model used. These can be compared with the experimental results of −61.6 Hz. For the ²J(H,H) coupling the theoretical results vary between −10.6 to −13.01 Hz. The indirect experimental result derived from partially deuterated liquid is −11.1 Hz. Inclusion of explicit hydrogen bonded molecules gives a small but important contribution. The vapor-to-liquid shifts are also considered. This shift is calculated to be negligible for ¹J(N,H) in agreement with experiment. This is rationalized as a cancellation of the geometry relaxation and pure solvent effects. For the chemical shielding, σ(15N) calculations at the B3LYP/aug-pcS-3 show that the vapor-to-liquid chemical shift requires the explicit use of solvent molecules. Considering only one ammonia molecule in an electrostatic embedding gives a wrong sign for the chemical shift that is corrected only with the use of explicit additional molecules. The best result calculated for the vapor to liquid chemical shift Δσ(15N) is −25.2 ppm, in good agreement with the experimental value of −22.6 ppm.